2000
DOI: 10.2466/pr0.2000.87.1.107
|View full text |Cite
|
Sign up to set email alerts
|

MMPI-2 Profiles of Colombian, Mexican, and Venezuelan University Students

Abstract: Performance of 82 Colombian, 87 Mexican, and 96 Venezuelan university students and adult community dwellers on Spanish translations of the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) were compared. Findings suggest more comprehensive research is required on applications of the MMPI-2 in Latin America and greater consideration of the roles of culture and nationality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Additionally, intelligence quotient, social status, and occupational status correlations influence the values reached in inmate population personality profiles (Holcomb & Adams, ; Holcomb, Adams, & Ponder, ; McDonald & Paitich, ). Culture and nationality are also sources of variability in the criminal personality (Boscán et al ., ; Catalá‐Miñana, Walker, Bowen, & Lila, ). More research is required to explain the relation among these variables with the groups studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, intelligence quotient, social status, and occupational status correlations influence the values reached in inmate population personality profiles (Holcomb & Adams, ; Holcomb, Adams, & Ponder, ; McDonald & Paitich, ). Culture and nationality are also sources of variability in the criminal personality (Boscán et al ., ; Catalá‐Miñana, Walker, Bowen, & Lila, ). More research is required to explain the relation among these variables with the groups studied here.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that differences in country of origin could play a role in personality profiles as measured by standardized assessments. Others (Boscán et al, 2000) found significant differences in Minnesota Multiphasic Personality Inventory–2 (MMPI–2; Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989) Spanish translation protocols according to country of origin in their sample of Mexican and Venezuelan college students and Colombian college students and community members. Thus, research indicates that country of origin in the context of personality assessment should be further explored.…”
Section: Personality Assessment Of Spanish-speakersmentioning
confidence: 99%
“…Specifically, AI/AN and Latinx people tend to score significantly higher on validity scales, particularly the L, clinical, content, and supplementary scales (Butcher et al, 2007; Greene et al, 2003; Hall & Phung, 2001). There are numerous Spanish language translations of the MMPI-2-RF (Boscán et al, 2000; Lucio et al, 1994; Velasquez et al, 2000), but the validity of translations still requires empirical attention. Among Latinx people, the findings related to the validity of the measure have been mixed.…”
Section: Summary Of Review Findingsmentioning
confidence: 99%